2017
DOI: 10.1097/md.0000000000008842
|View full text |Cite
|
Sign up to set email alerts
|

Inositol supplement improves clinical pregnancy rate in infertile women undergoing ovulation induction for ICSI or IVF-ET

Abstract: Objective:Pretreatment of myoinositol is a very new method that was evaluated in multiple small studies to manage poor ovarian response in assisted reproduction. This study was to determine the efficacy of myoinositol supplement in infertile women undergoing ovulation induction for intracytoplasmic sperm injection (ICSI) or in vitro fertilization embryo transfer (IVF-ET).Methods:A meta-analysis and systematic review of published articles evaluating the efficacy of myo-inositol in patients undergoing ovulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 35 publications
2
27
0
4
Order By: Relevance
“…Much research has focused on the role of myo-inositol as an insulin-sensitizing agent in polycystic ovary syndrome 88 and in improving oocyte quality and outcomes of assisted reproduction. 89 …”
Section: Myo-inositolmentioning
confidence: 99%
“…Much research has focused on the role of myo-inositol as an insulin-sensitizing agent in polycystic ovary syndrome 88 and in improving oocyte quality and outcomes of assisted reproduction. 89 …”
Section: Myo-inositolmentioning
confidence: 99%
“…Inositol has two major stereoisomers: myo-inositol (MYO) and Dchiro-inositol (DCI). MYO supplements have been observed to improve the metabolic profile and hyperandrogenism of women with PCOS [4,5], in addition to increasing the clinical pregnancy rate in infertile women undergoing ovulation induction for ICSI or IVF-ET, probably improving the quality of embryos and reducing the number of unsuitable oocytes [6]. However, a recent systematic review showed that MYO supplementation is not sufficient to improve oocyte maturation, embryo quality or the pregnancy rate [7].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, another review by Zheng et al stated that MI has a role in improving the number of good-quality embryos and reducing the number of germinal vesicles and degenerated oocytes. However, both PCOS and non-PCOS trials were included in their study [48].…”
Section: No Journal Authormentioning
confidence: 99%